Essentials of physical medicine and rehabilitation : musculoskeletal disorders, pain, and rehabilitation - Frontera, Walter R., 1955-; Silver, J. K. (Julie K.), 1965-; Rizzo, Thomas D., 1959- (Philadelphia, PA : Saunders/Elsevier)
Includes bibliographical references and index